Application of the Snowball Throwing Learning Model in Improving the Results and Learning Interest of Students at Pasirkuntul Elementary School - Euis Latipah; Lisda Aulia Apriani; Silvi Sofiatul Alawiyah; Tri Fatmah Nurhalizah (Penerbit Presisi Pustaka, 2025)
This study aims to describe in detail the application of the Snowball Throwing learning model by researchers directly in improving learning outcomes and learning interests of students at SDN Pasirkuntul. This learning model was chosen because it has active, fun characteristics, and encourages direct student involvement in the learning process. Snowball Throwing provides space for students to be actively involved in conveying and receiving information dynamically through throwing